49th AIAA Aerospace Sciences Meeting Including the New Horizons Forum and Aerospace Exposition 2011
DOI: 10.2514/6.2011-144
|View full text |Cite
|
Sign up to set email alerts
|

Development and Verification of the Charring Ablating Thermal Protection Implicit System Solver

Abstract: The development and verification of the Charring Ablating Thermal Protection Implicit System Solver is presented. This work concentrates on the derivation and verification of the stationary grid terms in the equations that govern three-dimensional heat and mass transfer for charring thermal protection systems including pyrolysis gas flow through the porous char layer. The governing equations are discretized according to the Galerkin finite element method with first and second order implicit time integrators. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 20 publications
1
27
0
Order By: Relevance
“…Still, all models (including RANS) are able to predict pressures that are within 1% of the peak pressure value. Along the attached boundary layer (gauges [31][32][33][34][35], all models show very similar results and are very close to the experiment, with the exception of gauges 31 and 35, where the gauges appear to be outliers due to the good performance of other surrounding gauges [2].…”
Section: Pressure and Heat Transfer Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Still, all models (including RANS) are able to predict pressures that are within 1% of the peak pressure value. Along the attached boundary layer (gauges [31][32][33][34][35], all models show very similar results and are very close to the experiment, with the exception of gauges 31 and 35, where the gauges appear to be outliers due to the good performance of other surrounding gauges [2].…”
Section: Pressure and Heat Transfer Resultssupporting
confidence: 79%
“…The charring ablator response (CHAR) code developed by Amar et al [32] was used. CHAR is a multidimensional thermal material response code used for solving ablating and nonablating TPS problems, as well as direct and indirect heat transfer problems.…”
Section: Time History Comparisonsmentioning
confidence: 99%
“…In addition, since the gas is eventually blown into the chemical reacting boundary layer [6], correct modeling of the pyrolysis gas is also important to help determine the surface boundary conditions. The gas flow within the charring ablator is often modeled as a porous media flow, for which steady-state Darcy's law is usually assumed [7][8][9][10]. For unsteady charring ablation problems, however, Weng and Martin [4] and Weng et al [5] showed that the steady state of Darcy's law is not necessarily valid for the whole geometry of small test articles used in arc-jet facilities.…”
mentioning
confidence: 99%
“…20 This code solves the charring ablator, general porous flow, and heat transfer problems in serial or parallel. In the present application, the tiles neither char nor ablate.…”
Section: Conduction Modelingmentioning
confidence: 99%